Students' Vocational High School Misconception Reviewed from Written Mathematical Communication Ability - Radiusman, Radiusman; Yurniwati, Yurniwati; Simanjuntak, Maslina; Sabariyah, Rizki Jamiatul; Nurmawanti, Iva (Universitas Islam Negeri Raden Intan Lampung, 2020)
This qualitative research aims to describe students’ misconceptions in linear programming reviewed from written mathematical communication ability. Four students from grade X SMKN 1 Purwasari were selected as research subjects by purposive sampling. Data collected through observation and essay tests. The results showed that the sample students experienced misconceptions in the low and high categories. Misconception with high categories lies in the indicators of changing mathematical ideas into mathematical models (75%), represent mathematical ideas into images or vice versa (100%), and mathematical problem-solving procedures (75%), while misconception with low categories is found in indicators choose the right concept in solving mathematical problems (25%). Based on this result, further treatment is needed to overcome students’ misconceptions before students continue learning to a higher stage.